Efektivitas Pelatihan Interaksi Ibu-Anak dalam Meningkatkan Kualitas Interaksi Ibu-Anak dan Compliance Anak - Devi Oktari Harvens; Linda Primana; Rini Hildayani (Jurnal Ilmiah Psikologi MIND SET, 2019)
This study aims to understand the effectiveness of mother-child interaction training in promoting child’s compliance during toddlerhood. Pair of mother and child aged from 14 to 36 months old and live in poor were involved as research subjects. The design of this study is one-group pretest-posttest design. The training was conducted for eight times within 15 days. The data collection was conducted before and after the training by recording activities into video format to be observed later. Mother-child interaction quality is assessed using Parenting Interactions with Children: Checklist of Observation Linked to Outcomes (PICCOLO), whilst compliance is assessed using Child Compliance Coding Manual: “Do” Context. Significance test using Wilcoxon Signed-Rank Test shows that there is a significant improvement in the score of mother-child interaction quality after the training conduct (p < 0,05), whilst child compliance shows improvement after the training conduct although not significantly (p > 0,05). The observation is explained in the results to see the changing of mother’s behaviour during the interaction and child compliance.